MelaNostrum: a consensus questionnaire of standardized epidemiologic and clinical variables for melanoma risk assessment by the melanostrum consortium. (14th September 2018) - Stratigos, Alexander J.; Fargnoli, Maria Concetta; De Nicolo, Arcangela; Peris, Ketty; Puig, Susana; Soura, Efthymia; Menin, Chiara; Calista, Donato; Ghiorzo, Paola; Mandala, Mario; Massi, Daniela; Rodolfo, Monica; et al.
Abstract: Background: Many melanoma observational studies have been carried out across different countries and geographic areas using heterogeneous assessments of epidemiologic risk factors and clinical variables. Aim: To develop a consensus questionnaire to standardize epidemiologic and clinical data collection for melanoma risk assessment. Methods: We used a stepwise strategy that included: compilation of variables from case–control datasets collected at various centres of the MelaNostrum Consortium; integration of variables from published case–control studies; consensus discussion of the collected items by MelaNostrum members; revision by independent experts; addition of online tools and image‐based charts; questionnaire testing across centres and generation of a final draft. Results: We developed a core consensus questionnaire (MelanoQ) that includes four separate sections: A. general and demographic data; B. phenotypic and ultraviolet radiation exposure risk factors and lifestyle habits; C. clinical examination, medical and family history; and D. diagnostic data on melanoma (cases only). Accompanying online tools, informative tables, and image‐based charts aid standardization. Different subsections of the questionnaire are designed for self‐administration, patient interviews performed by a physician or study nurse, and data collection from medical records. Conclusions: The MelanoQ questionnaire is a useful tool for the collection and standardization of epidemiologic and clinical data across different studies, centres, cultures and languages. This will expedite ongoing efforts to compile high‐quality data for pooled analyses or meta‐analyses and offer a solid base for the design of clinical, epidemiologic and translational studies on melanoma.